EFEKTIVITAS PERDA KOTA SOLOK MENGENAI PENDIRIAN BANGUNAN DALAM PERSPEKTIF HUKUM TATA NEGARA (Studi Kasus di Kelurahan Pasar Pandan Air Mati Kecamatan Tanjung Harapan) - Rahmat Dani Saputra; Sudi Prayitno (Jurnal Integrasi Ilmu Syariah (Jisrah), 2020)
The main problem in this study is the effectiiveness of Solok City regional regulations regarding building construction. The purpose of this discussion is to find out the riles set by the Solok City government regarding building construction and building permit regulations in Solok City in realizing a beautiful, orderly, simple integrated Solok City arrangementKeyword: efektivitas,Perda, hukum tata negara